2021
DOI: 10.1523/jneurosci.1202-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus–Prefrontal Coupling Regulates Recognition Memory for Novelty Discrimination

Abstract: Recognition memory provides the ability to distinguish familiar from novel objects and places, and is important for recording and updating events to guide appropriate behavior. The hippocampus (HPC) and medial prefrontal cortex (mPFC) have both been implicated in recognition memory, but the nature of HPC-mPFC interactions, and its impact on local circuits in mediating this process is not known. Here we show that novelty discrimination is accompanied with higher theta activity (4-10 Hz) and increased c-Fos expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 70 publications
1
26
1
Order By: Relevance
“…We found that the power of vHPC theta oscillations increases during object exploration, suggesting that vHPC theta oscillations in this task might be associated with the cognitive processes underlying the behavioral response. In addition, several studies reported an increase of mPFC theta power during decision making, attentional processes, and, recently, in a NOR task ( 23 , 46 , 47 ). We observed an increase in mPFC theta power during the exploration of the contextually incongruent object.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We found that the power of vHPC theta oscillations increases during object exploration, suggesting that vHPC theta oscillations in this task might be associated with the cognitive processes underlying the behavioral response. In addition, several studies reported an increase of mPFC theta power during decision making, attentional processes, and, recently, in a NOR task ( 23 , 46 , 47 ). We observed an increase in mPFC theta power during the exploration of the contextually incongruent object.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the anatomical connectivity and pharmacological experiments, we predicted that the resolution of the task would involve tight communication between both structures. Increased theta vHPC-mPFC connectivity has been observed in spatial navigation, working memory ( 17 , 48 ), a NOR task, and rewarded object–context associations ( 25 , 47 , 49 ). Consistently, we found that the vHPC and mPFC share an increase in theta activity irrespective of the explored object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LFP recordings from the mPFC in ex-vivo slices have hinted toward synchronized activity between the PL and IL ( Van Aerde et al., 2008 ). We thus investigated coupled activity between the PL and IL across behavioral states using cross-correlation analysis ( Adhikari et al., 2010 ; Wang et al., 2021 ). This method assumes that functional connectivity between the two structures is accompanied by reasonably coherent activity within a specific frequency range.…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal theta and gamma rhythms have been associated with novelty recognition (Penley et al, 2013;Kitanishi et al, 2015;Zheng et al, 2016;Brown et al, 2020;Kragel et al, 2020;Park et al, 2021;Wang et al, 2021). Since social stimuli have been shown to increase hippocampal theta and gamma oscillations (Tendler and Wagner, 2015;Villafranca-Faus et al, 2021;Brown et al, 2020) and mouse models of social dysfunction have been associated with alterations in hippocampal oscillations at both frequencies (Arbab et al, 2018;Aoki et al, 2017;Cheaha and Kumarnsit, 2015), we examined theta and gamma power in the vCA1 of WT and Shank3B KO mice in the presence of a novel mouse.…”
Section: Discussionmentioning
confidence: 99%